Peramalan Beban Listrik Kabupaten Pesisir Selatan Dengan Analisis Regresi - Hendri, Zulka; Efendi, Efendi; Asrul, Junaidi; Fitriadi, Fitriadi (Elektron : Jurnal Ilmiah, 2023)
The more electric vehicles emerge, the more electricity demand will increase in each region. This will encourage electricity providers to increase the number or capacity of generators. The construction of a new power plant requires load forecasting to determine how much capacity the plant will build. This study aims to predict the electrical load in Pesisir Selatan, West Sumatra until 2031 using linear regression analysis and time series. Forecasting is done on each sector of PLN customers. Forecasting is done based on the PLN customer sector. The forecasting sectors are the household, business, social and government sectors. The four test criteria were carried out are namely the coefficient of determination test (R2), the F test, the T test and the mean absolute percentage error (MAPE). The forecasting results show that in 2031 the electricity load for the household sector is 120.1 MW, the business sector is 5.7 MW, the social sector is 56.9 MW and the government is 9.5 MW.